EQUATORIAL TOTAL ELECTRON CONTENT’S (TEC) REACTION TO GEOMAGNETIC STORM EVENTS FROM JANUARY TO MARCH 2020 - Adebayo, Samuel; Ajide, Adeolu Bamidele; Babatola, Babatunde Keji (Science Heritage Journal)
This study looked at the behaviour of Equatorial Total Electron Content (TEC) in connection to geomagnetic storms that occurred between January and March of 2020. The data used in the study came from the Global Positioning System (GPS). Vertical Total Electron Content (VTEC) data was collected at three different ground stations to conduct the investigation: NKLG (GMAGLat. -8.04°S, GMAGLong. 81.05°E), ADIS (GMAGLat. 1.13°N, GMAGLong. 110.47°E), and DJIG (GMAGLat. 3.36°N, GMAGLong. 11457°E). The locations were carefully chosen in order to offer a comprehensive picture of the equatorial ionosphere’s response to magnetic storms. The study’s findings show that the equatorial region undergoes both amplification and depletion effects in the reaction of TEC to geomagnetic storms. The paper also proposed possible approaches to clarify these findings. The three stations’ different latitudinal positions were recognised as the principal source of the considerable variations in GPS-TEC responses during storm periods. Furthermore, during the storm periods, the peak positive percentage deviation of TEC displayed an ascending trend with rising altitude for each monitoring station. This finding suggests the existence of complex height-related interactions between the equatorial ionosphere and geomagnetic storms. The current study examines the complicated factors that influence the behaviour of TEC in equatorial regions during geomagnetic storms. It highlights the need of adding latitudinal and altitude factors in such studies.